Forms on vector bundles over three-dimensional hyperbolic spaces and black hole geometry - Bytsenko, A. A. [UNESP]; Guimarães, M. E.X. [UNESP]; Helayel-Neto, J. A. (World Scientific Publishing, 2006)
We consider gauge fields and tensor kernels based on differential p–forms on real hyperbolic manifolds. The spectral functions of the topological invariant of three–dimensional black hole manifolds associated with physical degrees of freedom of the Hodge-de Rham operators are analyzed.